Hubungan Motivasi dengan Kinerja Perawat di Ruang Instalasi Perawatan Rumah Sakit - Ayatulloh, Daviq; Twistiandayani, Retno; Basri, Ahmad Hasan (Indonesian Academia Health Sciences Journal, 2021)
Work motivation is motivated by the need in a person to influence the person's behavior, High motivation a person is expected to lead to positive behaviors that will ultimately result in good performance in the work. One that is often the cause of reduced performance is the lack of internal and external motivation in the work. The design of this study using cross-sectional methods. The sampling method used is Probability Sampling. Samples taken by 35 respondents are nurses who work in the Inpatient Room RSI Sakinah Mojokerto, in May 2014. Research data was taken using a questionnaire. After the tabulated data were analyzed using the Spearman Rho test with significance level 0.05. The results showed motivation of nurses working in the high category by 23 respondents (65.7%), medium category by 8 respondents (22.9%) and low category by 4 respondents (11.4%). Performance nurse with excellent categories by 20 respondents (57.1%), both as a category 4 respondents (11.4%), pretty much as 5 categories of respondents (14.3%), less as category 2 respondents (5.7% ), and less so by 4 categories of respondents (11.4%). While the results obtained from the statistical tests no correlation with the performance of work motivation nurses with correlation value of 0.728 with a significance level of 0.000 (ρ <0.05). Seeing these results it is necessary to coaching head office and nurse by providing training to improve motivation and performance so nurses can lead to good service and a good image for the hospital in the community.